Preparation of Cu/ZnO/M2O3 (M = Al, Cr) catalyst to stabilize Cu/ZnO catalyst in methanol dehydrogenation - Jung, KD; Joo, OS (SPRINGER, 2002)
ZnO reducibility in three component catalysts was monitored in a methanol stream by a microbalance. The ZnO in the Cu/ZnO is reduced in the methanol stream from ca 500 K, but the addition of a third component to Cu/ZnO can suppress the reduction of ZnO. The Cu/ZnO/Cr2O3 prepared from a hydrotalcite-like precursor shows high stability in methanol dehydrogenation. The high stability of Cu/ZnO/Cr2O3 is due to the stabilization of ZnO by formation of ZnCr2O4 even in the reduced condition.
Keywords: ZNO